PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN SENI TARI DI KELAS VII 3 SMP NEGERI 13 PADANG - Putri Oktavia; Yuliasma Yuliasma; Susmiarti Susmiarti (SENDRATASIK UNP, 2018)
AbstractThis study aims to increase students' activities and learning outcomes by describing the use of cooperative learning models of STAD type in dance art learning of 7th-grade students of SMP 13 Padang. This type of research was classroom action research. The object of the study was 32 7th grade students of SMP 13 Padang. Techniques of data collection were in the form of literature study, observation, tests, assignments and documentation. The results show that the use of cooperative learning models of STAD type in dance art learning which was carried out in two cycles went well. (1) Student learning activities with indicators of; asking questions, brave opinions, doing assignments, not making noise in class, and not going in and out of class, in the first cycle, the overall average score was 64.3%. In cycle II the overall average score increased to 80%. (2) Students` learning outcomes reach very good criteria. It can be seen from the results of written tests in cycle I with an average score of 77.7 and in cycle II increased to 84. Then the results of the students' practical ability in cycle I with an average score of 76, 2 and in the second cycle increased to 87.8. Thus, it can be concluded that the use of cooperative learning models of STAD type in the dance learning can increase student activity and learning outcomes. Keywords: Usage, STAD Type, Learning Outcomes, Dance Learning